Phylogenetic relationships among tetraploid species of Bellevalia (Asparagaceae) endemic to south-central Mediterranean. (2nd November 2017) - Astuti, G.; Brullo, S.; Domina, G.; El Mokni, R.; Giordani, T.; Peruzzi, L.
Abstract: In the south-central Mediterranean four tetraploid species of Bellevalia occur: B. dolichophylla, B. galitensis, B. mauritanica, and B. pelagica . Another group of plants, morphologically similar to B. dolichophylla, has been recently recovered in Zembra Island (Tunisia). A phylogenetic reconstruction involving all these tetraploid taxa was performed using both plastidial and nuclear markers ( trn L- trn F and ITS, respectively). For all these taxa, an allopolyploid origin involving B. romana and B. dubia is supported. Regarding plants from Zembra, they may fall within the variability of B. dolichophylla .